Μετάφραση : «Toxicological Risk Assessment of Lead (Pb) Contamination in Public Water System in Lagos Metropolis, Nigeria», Olusola Togunde, Tam-Miette Dawari Briggs, Nnamdi Henry Amaeze, Henry Ebele Obanya του Environmental Toxicology and Pollution Management Unit, Department of Zoology, University of Lagos, Lagos, Nigeria που δημοσιεύθηκε Online το 2019 στο Journal of Environmental Protection. - (:unkn) unknown (My University, 2021)
Μετάφραση έρευνας με θέμα την εκτίμηση του κινδύνου μόλυνσης από μόλυβδο στο Λάγκος της Νιγηρίας και τις επιπτώσεις αυτής.

Translation of a study about the risk assessment of lead contamination in Lagos, Nigeria and it's effects.
Translation: : «Toxicological Risk Assessment of Lead (Pb) Contamination in Public Water System in Lagos Metropolis, Nigeria», Olusola Togunde, Tam-Miette Dawari Briggs, Nnamdi Henry Amaeze, Henry Ebele Obanya Environmental Toxicology and Pollution Management Unit, Department of Zoology, University of Lagos, Lagos, Nigeria as published online in 2019 on Journal of Environmental Protection.
Keywords: μόλυβδος, Λάγκος, Νιγηρία; lead, Lagos, Nigeria